Planificaciones microcurriculares en el área de informática desarrolladas por los docentes del subnivel superior de educación general básica en instituciones educativas particulares de la ciudad de Loja durante el año lectivo 2023-2024. - Campoverde Chalán, Kerllys Brisseth (2024)
In the educational context, micro-curricular planning is considered indispensable to achieve pedagogical success and fulfill the objectives established in the curriculum. For this reason, the need to investigate this topic in depth is justified, giving way to the research "Micro-curricular planning in the area of computer science developed by teachers of the higher sub-level of general basic education in private educational institutions in the city of Loja during the school year 2023-2024". The methodology used, in coherence with the Regulations of the Academic Regime, article 216 of the National University of Loja of the year 2021, was based on the deductive method with quantitative approach, with a transversal research design and exploratory-descriptive scope, the population considered were the micro-curricular plans of the subjects related to informatics, provided by the eight educational institutions that participated in the research. The results of the research reveal that the educational institutions have the following subjects related to computer science: mathematics, robotics, digital technologies and computing, for which the teachers develop micro-curricular plans by didactic unit, according to the instructions to elaborate the annual curricular planning and the micro-planning from the National System of Education of Ecuador given by the Ministry of Education, Keywords: micro-curricular planning, informatics, curriculum planning, informatics in education.